IDENTIFIKASI MANFAAT LIMBAH BATANG TEMBAKAU DI KABUPATEN LOMBOK TIMUR: Pengelolaan Limbah Pertanian Dengan Konsep Eco-Farming - Anwar, Muhammad; Murah; Muhammad Zainuddin (LPPM Universitas Gunung Rinjani, 2021)
Post-harvest management of tobacco commodities in East Lombok Regency is very important considering that the waste of tobacco stems, leaf stalks, seeds, and residues from the oven process still contains nicotine. Efforts need to be made to treat tobacco waste so that harmful risks can be reduced by applying the concept of environmentally friendly agriculture or an eco-farming system. Environmentally friendly agriculture is part of the implementation of sustainable agriculture, which is an agricultural movement that uses ecological principles, the study of the relationship between organisms and their environment. East Lombok's local resources in the form of the availability of tobacco stem waste which is abundant, neglected, and damaging to the aesthetics of the environment requires more in-depth attention to study its benefits into various environmentally friendly products. This research was conducted using a qualitative descriptive method with a library research approach. The benefits of tobacco stem waste are as follows: Tobacco stem and stem waste as bio-biket material; Tobacco stems and seeds as biodiesel; Tobacco waste extract granules against aedes aegypti larvae; Tobacco stem waste as biopesticide material; Tobacco stem waste as organic fertilizer; Tobacco stem waste as natural dye for batik and bioinsecticide tobacco stem soaking water. Keywords: Waste, Tobacco Stems, Eco-Farming and East Lombok ABSTRAK Pengelolaan pasca panen komoditas tembakau di Kabupaten Lombok Timur sangat penting dilakukan mengingat limbah batang tembakau, tangkai daun, biji, dan residu dari proses pengovenan masih mengandung nikotin. Perlu dilakukan upaya pengolahan limbah tembakau tersebut agar resiko berbahaya dapat dikurangi dengan menerapkan konsep pertanian yang ramah lingkungan atau eco-farming system. Pertanian ramah lingkungan adalah bagian dari impelementasi pertanian berkelanjutan (sustainable agriculture) yaitu gerakan pertanian yang menggunakan prinsip ekologi, studi hubungan antara organisme dan lingkungannya. Sumberdaya lokal Lombok Timur berupa tersedianya limbah batang tembakau yang melimpah, tidak terurus, dan merusak estetika lingkungan membutuhkan perhatian yang lebih mendalam untuk dikaji manfaatnya menjadi berbagai produk yang ramah lingkungan. Penelitian ini dilakukan dengan metode deskriptif kualitatif dengan pendekatan studi pustaka (library research). Manfaat limbah batang tembakau sebagai berikut: Limbah batang dan gagang (stem) tembakau sebagai bahan bio-biket; Batang dan biji tembakau sebagai biodesel; Granul ekstrak limbah tembakau terhadap larva aedes aegypti; Limbah batang tembakau sebagai bahan biopestisida; Limbah batang tembakau sebagai pupuk organik; Limbah batang tembakau sebagai pewarna alami batik dan Air rendaman batang tembakau bioinsektisida. Kata kunci: Limbah, Batang Tembakau, Eco-Farming dan Lombok Timur